$$\hbox {H}_2$$ -roaming dynamics in the formation of $$\hbox {H}_{3}^{+}$$ following two-photon double ionization of ethanol and aminoethanol - Aaron Ngai; Sebastian Hartweg; Jakob D. Asmussen; Björn Bastian; Matteo Bonanomi; Carlo Callegari; Miltcho Danailov; Michele di Fraia; Raimund Feifel; Sarang Dev Ganeshamandiram; Sivarama Krishnan; Aaron LaForge; et al. (Scientific Reports)
Abstract Roaming reactions involving a neutral fragment of a molecule that transiently wanders around another fragment before forming a new bond are intriguing and peculiar pathways for molecular rearrangement. Such reactions can occur for example upon double ionization of small organic molecules, and have recently sparked much scientific interest. We have studied the dynamics of the $$\hbox {H}_2$$ -roaming reaction leading to the formation of $$\hbox {H}_3^+$$ after two-photon double ionization of ethanol and 2-aminoethanol, using an XUV-UV pump-probe scheme. For ethanol, we find dynamics similar to previous studies employing different pump-probe schemes, indicating the independence of the observed dynamics from the method of ionization and the photon energy of the disruptive probe pulse. Surprisingly, we do not observe a kinetic isotope effect in ethanol- $$\hbox {D}_6$$ , in contrast to previous experiments on methanol where such an effect was observed. This distinction indicates fundamental differences in the energetics of the reaction pathways as compared to the methanol molecule. The larger number of possible roaming pathways compared to methanol complicates the analysis considerably. In contrast to previous studies, we additionally analyze a broad range of dissociative ionization products, which feature distinct dynamics from that of $$\hbox {H}_{3}^{+}$$ and allow initial insight into the action of the disruptive UV-probe pulse.